Organic silicon in the acceleration of tissue healing in wound healing by secondary intention (Revista Contexto & Saúde, 2025)
Objective: To evaluate the efficacy and safety of different concentrations of organic silicon in tissue repair in wounds with healing by second intention. Methodology: A total of 27 Wistar rats were divided into five groups: Control (n=5), Hydrogel (n=5), 5% Silicon (n=5), 10% Silicon (n=6), and 15% Silicon (n=5). For this purpose, incision and dissection of the tissue were performed in the region of the dorsal midline close to the scapulae, up to the muscular fascia (2 cm² area). Following this, the wound was cleaned daily with saline and gauze in all animals, with subsequent treatment with organic silicon at concentrations of 5%, 10%, and 15%, and hydrogel, respectively. At the end of 23 days, euthanasia and blood collection for hematological and biochemical analysis were performed. Results: Treatment with 15% organic silicon was more effective in shedding the crust and in tissue repair of the lesion. The safety of silicon in the treatment of wounds was demonstrated from laboratory tests that did not indicate hematological, hepatic, and renal toxicity with the proposed treatment. Conclusion: It was found that 15% organic silicon is effective in accelerating wound healing by second intention and has not shown any toxic effect on hematological, metabolic, hepatic, and renal parameters.
Keywords: Silicon; Wound Healing; Rats Wistar; Treatment